Studies of Bioactivities of Adansonia digitata (L.) (Dhaka University Journal of Pharmaceutical Sciences, 2016)
The methanol extracts of leaves and barks of Adansonia digitata (L.) and their organic and aqueous soluble partitioning materials were evaluated for antioxidant, cytotoxic, thrombolytic, membrane stabilizing, antimicrobial, analgesic, and antidiarrhoel activities. In the DPPH free radical scavenging assay, the aqueous soluble materials of bark and leaves of A. digitata displayed the highest free radical scavenging activity with IC50 values of 2.21 ?g/ml and 7.70 ?g/ml, respectively while the crude extract of leaves and its pet ether soluble fraction showed significant lethality to brine shrimps having LC50 value of 6.99 and 0.284 ?g/ml, respectively as compared to standard vincristine sulphate (LC50 value of 0.44 ?g/ml). During assay for thrombolytic activity of human blood clot, the carbon tetrachloride soluble partitionate of leaves of A. digitata revealed 48.11% clot lysis. In the membrane stabilizing assay, the carbon tetrachloride- and aqueous-soluble fractions of methanol extract of leaves inhibited 61.52 % and 16.03 % hypotonic solution- and heat-induced haemolysis of RBCs, respectively. The methanolic extracts of leaves and barks of A. digitata revealed significant central and peripheral analgesic activity at 200 and 400 mg/kg body weight. The crude extract of leaves of A. digitata also displayed significant antidiarrhoel but mild antibacterial activities.Dhaka Univ. J. Pharm. Sci. 14(2): 157-162, 2015 (December)